Development of comics as a learning media on human digestive system topic - Febi Fitria Nuraini; Lise Chamisijatin; Eko Susetyarini; Moch. Agus Krisno Budiyanto; Dwi Setyawan (Research and Development in Education (RaDEn), 2021)
The human digestive system is a difficult subject for high school students. The purpose of this research was to develop comics as a learning media on the human digestive system topic. The development of comics used the Sugiyono model which consists of the stages of identifying potentials and problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing, and product revision. The participants involved in the product trial were seventh grade students of SMP Diponegoro and SMP Raden Fatah in Batu City. The data collection instruments used were validation sheets and test sheets. The results of the validation from content and media experts inform that comics were included in the appropriate category. The average of students' posttest results were always greater than the pretest, both on small-scale and large-scale trials. Student responses to comics were also categorized as very positive. In conclusion, the comics developed are effective and feasible to use.